Composition, acquisition, and distribution of the Vi exopolysaccharide-encoding Salmonella enterica pathogenicity island SPI-7. - Pickard, D; Wain, J; Baker, S; Line, A; Chohan, S; Fookes, M; Barron, A; Gaora, P; Chabalgoity, J; Thanky, N; Scholes, C; Thomson, N; et al. (2003)
Vi capsular polysaccharide production is encoded by the viaB locus, which has a limited distribution in Salmonella enterica serovars. In S. enterica serovar Typhi, viaB is encoded on a 134-kb pathogenicity island known as SPI-7 that is located between partially duplicated tRNA(pheU) sites. Functional and bioinformatic analysis suggests that SPI-7 has a mosaic structure and may have evolved as a consequence of several independent insertion events. Analysis of viaB-associated DNA in Vi-positive S. enterica serovar Paratyphi C and S. enterica serovar Dublin isolates revealed the presence of similar SPI-7 islands. In S. enterica serovars Paratyphi C and Dublin, the SopE bacteriophage and a 15-kb fragment adjacent to the intact tRNA(pheU) site were absent. In S. enterica serovar Paratyphi C only, a region encoding a type IV pilus involved in the adherence of S. enterica serovar Typhi to host cells was missing. The remainder of the SPI-7 islands investigated exhibited over 99% DNA sequence identity in the three serovars. Of 30 other Salmonella serovars examined, 24 contained no insertions at the equivalent tRNA(pheU) site, 2 had a 3.7-kb insertion, and 4 showed sequence variation at the tRNA(pheU)-phoN junction, which was not analyzed further. Sequence analysis of the SPI-7 region from S. enterica serovar Typhi strain CT18 revealed significant synteny with clusters of genes from a variety of saprophytic bacteria and phytobacteria, including Pseudomonas aeruginosa and Xanthomonas axonopodis pv. citri. This analysis suggested that SPI-7 may be a mobile element, such as a conjugative transposon or an integrated plasmid remnant.